An introduction to developmental psychology - Slater, Alan; Bremner, J. Gavin 1949- (John Wiley & Sons Inc., 2017)
An Introduction to Developmental Psychology, 3rd Edition is a representative and authoritative 'state of the art' account of human development from conception to adolescence. The text is organised chronologically and also thematically and written by renowned experts in the field, and presents a truly international account of theories, findings and issues. The content is designed with a broad range of readers in mind, and in particular those with little previous exposure to developmental psychology.